Probiotic potential of Lactobacillus plantarum with the cell adhesion properties - Abhinandan Patil (Journal of Global Pharma Technology, 2018)
The use of microbes as functional food maintain health and prevent many disease and disorder. The isolation and research of new strains of probiotic strains especially lactobacilli proven to be useful to satisfy the increasing demand of the population. In the current study, the probiotic potential of Lactobacillus strains isolated from sheep milk was investigated. The Lactobacillus strains were identified and evaluated for tolerance against gastric acidity and bile toxicity, along with the adhesion to HT-29 cells. The study proved the antimicrobial activities and antibiotic susceptibility. Survival of the strains through the host intestine was examined by the 12 week Wister rat feeding and faecal analysis trial. The in-vivo trials not only proved the adhesion but also the survival of the Lactobacillus plantarum MCC 3595 inside the intestinal lumen of the host. Thus, the isolated strain can act as the functional food by the further clinical investigation.